Patologi Sosial Dalam Pandangan Islam - Novita Taneu (Jurnal Al-Manar, 2022)
Abstract: Social pathology is the science of social symptoms that are considered "sick", caused by social factors or the science of origins and characteristics, diseases related to the nature of human existence in people's lives. The research design used is the Literature Review method or literature review. The object of research in this study is the internet, journals, the Koran and handbooks which are related to the problem or theme raised by the author. The data obtained in conducting this research is by using the internet and research journals that have been done previously. This study shows that social pathology is one of the problems that Islam pays attention to. Various kinds of problems have been described in the Qur'an to solve this problem, for example providing punishment for people who commit theft, drinking, killing, and others as a reward for people who do a problem that is contrary to Islamic law.